2013
DOI: 10.1177/1359105313488976
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality on reported pain and self-efficacy for pain management in older cancer patients

Abstract: This study examines the relationship of personality traits and affect on cancer-related pain in 150 older adults receiving outpatient treatment at a comprehensive cancer center. Regression analyses revealed extraversion as a significant predictor of current pain, with openness to experience as a significant indicator of average pain. Similarly, positive affect and negative affect were significant predictors of self-efficacy for pain management. Moderation models showed that conscientiousness and extraversion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…These results confirm what other studies have found about the negative influence of neuroticism on cancer patients' health ( Hulbert-Williams et al., 2012 ; Van Esch et al., 2012 ). Neuroticism has been related to physical symptoms of the disease, such as pain expression and fatigue ( Krok and Baker, 2014 ; Wang et al., 2013 ). Furthermore, presenting neurotic personality characteristics might lead to a poorer psychological and mental health, as people tend to experience life events as more threatening and distressing ( Perry et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results confirm what other studies have found about the negative influence of neuroticism on cancer patients' health ( Hulbert-Williams et al., 2012 ; Van Esch et al., 2012 ). Neuroticism has been related to physical symptoms of the disease, such as pain expression and fatigue ( Krok and Baker, 2014 ; Wang et al., 2013 ). Furthermore, presenting neurotic personality characteristics might lead to a poorer psychological and mental health, as people tend to experience life events as more threatening and distressing ( Perry et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, presenting neurotic personality characteristics might lead to a poorer psychological and mental health, as people tend to experience life events as more threatening and distressing ( Perry et al., 2018 ). In short, as can be seen, neuroticism is associated with an increased risk of poorer mental health outcomes ( Krok and Baker, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings regarding the relationship between other traits (extraversion, openness, conscientiousness) and self-reported pain and fatigue are inconsistent. 35, 36 Such inconsistent findings may be explained in part by different sample characteristics and measures. However, it is possible that the integrated LPA approach used in the present study helps clarify the trait-based approaches used in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Search terms included personality, five-factor model, ten-item personality inventory, affect in combination with either cancer, cancer patient(s), older adult(s), elderly, race, and race differences. Results of this extensive literature search found only three studies that examined personality traits among cancer patients [22][23][24]. Findings from these studies were limited by: the lack of consistency in how personality was defined (not based on the FFM), wide range in patients' ages, and a lack of inclusion of diverse race groups to explore personality traits.…”
Section: Race and Personalitymentioning
confidence: 99%